(3CbVjI GdQShd Udi Gddg Ydjg hSde eeG bVi Hg Ch CeQ HGdbVGA ajgs - (3eMeO Hf CMeO Hf CHj HcQ Hf aQM GdCfUGQj GdNRQLj GdCfOdSj, CHh YHO Gddg, GdbQWHj,J (B671 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO Hf aQL gPG cJGH GPcQ ajg Gf TGA Gdgd eG GfJgi Edi ef GbVjI QShd Gddg Udi Gdgd Ydjg hSde GdJi bVGgG ChGeQ HGdbVGA ajgG s
(3BNQgG (B:s
(3hMOKfi HGdeSJNQLI Gdabjg CHh GdeWQa YHO GdQMef QMeg Gddg Ydjge GLeYjf Gejf QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HdZ ebGHdI Ydi GdCUd GdefShN efgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B239s
Keywords: (3GdMOjK h GdeUWdMs